Potensi Antiinflamasi Daun Dollu (Dodonaea Viscosa L.): Studi In Vivo Pada Model Edema Karagenan Tikus Putih (Rattus Norvegicus) - Azzahra Vivin Mahdiya Afandy; Angga Bayu Budiyanto; Lukman Hardia (Universitas Pahlawan Tuanku Tambusai, 2026)
potential plant is dollu leaf (Dodonaea viscosa L.), which reportedly contains a variety of secondary metabolites, such as flavonoids, alkaloids, tannins, saponins, and phenolic compounds that are thought to play a role in inhibiting the inflammatory response. Objective to assess the anti-inflammatory activity of dollu leaf ethanol extract (D. viscosa L.) in male white rats with carrageenan-induced inflammation. Methods the study was conducted using a laboratory experimental design with a model of foot edema induced by a 1% carrageenan solution. The experimental animals were divided into five groups, namely negative control, positive control, and three treatment groups that received dollu leaf ethanol extract with doses of 125, 250, and 500 mg/kg body weight. Observation of edema volume was carried out every one hour for six hours using a plethysmometer. All data were statistically analyzed using the One-Way ANOVA test followed by the Least Significant Difference follow-up test at the significance level of p < 0.05. Results dollu leaf ethanol extract showed increased anti-inflammatory activity over observation time. Compared to negative controls, doses of 125 and 250 mg/kgBB showed significant differences from the first hour (p=0.024 and p=0.006), while all doses showed very significant edema inhibition from the third hour to the sixth hour (p<0.001). Against positive controls, the dose of 250 mg/kgBB still showed a difference in the first to fourth hours (p=0.010–0.045), but at the fifth and sixth hours the entire dose did not differ significantly (p>0.05), showing an efficacy of the extract comparable to standard drugs in the advanced inflammatory phase. The dose of 250 mg/kg BB provides the most consistent anti-inflammatory response compared to other doses. Conclusion dollu leaf ethanol extract (D. viscose L.) It has been proven to provide a significant anti-inflammatory effect in suppressing the formation of edema due to carrageenan induction in male white rats. This activity is mainly seen in the advanced inflammatory phase and the dose of 250 mg/kg BB is the dose that shows the most optimal effectiveness, so this extract has the potential to be developed as an anti-inflammatory phytopharmaceutical candidate.